Refining the HIV-1 glycan shield model: dynamics of a heterogeneous envelope trimer and empirical prediction of glycan processing - Garrard, Clare (Department of Integrative Biomedical Sciences (IBMS), 2020)
The HIV-1 surface protein, Envelope (Env), is covered in asparagine-linked glycans, which interact with the human immune system and are thus important as potential vaccine targets. Laboratory studies have shown that the glycan type and form can differ substantially at each glycan site on Env clones. However, these studies are limited by time and cost and rely on biosynthetic assumptions to elucidate the structure of branched glycans. Furthermore, glycan heterogeneity creates challenges when determining the three-dimensional structure of Env, which has resulted in the use of methods that restrict glycan processing to produce uniform glycans for these studies. Computational methods are used to complement the laboratory studies; however, due to the limitations of modelling software, even computational studies have focussed on uniformly glycosylated Env models using a limited set of high-mannose glycans, rather than a mix of glycan types. To bridge this gap, this study set out to examine the structural differences of two computationally glycosylated HIV-1 Env trimers, one uniformly glycosylated, and the other based on the heterogeneous glycosylation of a laboratory determined gp160 strain. A secondary aim was to estimate whether the type of glycan is predictable using computational techniques, since these are less expensive and time consuming than laboratory studies. Using 500 ns molecular dynamics (MD) simulations, it was found that the heterogeneously glycosylated trimer had 64% greater stability, likely due to the presence of 25% more hydrogen bonds, as well as stabilising bonds which appeared to prevent asymmetrical movements. Furthermore, by focussing on the heterogeneously glycosylated trimer, a computational method based on surface area was explored to estimate the accessibility to enzymes involved in glycan processing, and to use this measure as a predictor of the glycan type. The results of this study highlight the differences between a uniformly, and a heterogeneously, glycosylated trimer, and suggest that previous MD studies, which used uniformly glycosylated trimers, may not sufficiently describe the structural dynamics of HIV-1 Env. Notably, complex glycans appear to stabilise the trimer to a greater extent than the high-mannose glycans used in previous studies. Thus, it is evident that research on Env models should incorporate a more diverse set of glycans in order to deepen our understanding of the dynamics of Env, which will, in turn, further our understanding of its interactions with antibodies and anti-HIV compounds.